2021
DOI: 10.1186/s12887-021-03036-w
|View full text |Cite
|
Sign up to set email alerts
|

Brain and renal oxygenation measured by NIRS related to patent ductus arteriosus in preterm infants: a prospective observational study

Abstract: Background Patent ductus arteriosus (PDA) is common among preterm neonates. Haemodynamically significant ductus arteriosus (hsPDA) can cause ductal steal and contribute to poor outcomes. Our aim was to evaluate ductus arteriosus patency and significance using two-site near-infrared spectroscopy (NIRS) measurements in preterm infants older than 72 h as a supplemental tool to echocardiography. Methods In this prospective observational study, 123 pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…The optimal period of monitoring of Rsat for AKI prediction may be earlier than the time the echocardiogram was obtained; for example, a prior study found that low Rsat during the first day of life was associated with the development of AKI on day 2 to day 7. 2 Although we expected lower renal saturations in the hsPDA group, as demonstrated previously, 8,22 there have been differing results in other studies, which have shown no correlation between Rsat and hsPDA. 23 This may reflect the variability among patient populations.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The optimal period of monitoring of Rsat for AKI prediction may be earlier than the time the echocardiogram was obtained; for example, a prior study found that low Rsat during the first day of life was associated with the development of AKI on day 2 to day 7. 2 Although we expected lower renal saturations in the hsPDA group, as demonstrated previously, 8,22 there have been differing results in other studies, which have shown no correlation between Rsat and hsPDA. 23 This may reflect the variability among patient populations.…”
Section: Discussionsupporting
confidence: 56%
“…Although we expected lower renal saturations in the hsPDA group, as demonstrated previously [8,22], there have been differing results in other studies, which have shown no correlation between Rsat and hsPDA [23]. This may reflect the variability among patient populations.…”
Section: Accepted Manuscriptsupporting
confidence: 51%
“…Our study found a 42% incidence of AKI in those with hsPDA, which is higher than the reported incidence of 34% 3 . Although we hypothesized lower renal saturations in the hsPDA group, as demonstrated previously 8, 23 , there have been studies that have shown no correlation between Rsat and hsPDA 24 . This may re ect the variability among patient populations.…”
Section: Discussionmentioning
confidence: 48%
“…Some clinical studies demonstrated a faster and marked deterioration of renal oxygenation and blood flow in the presence of hsPDA, comparing with no effect or less apparent effect on brain oxygenation and perfusion [35,36]; therefore, it is likely that medical treatment-related closure or constriction of PDA primarily improves renal oxygenation and blood circulation. Moreover, the ductal shunt occurs predominantly from the lower rather than the upper body circulation [37].…”
Section: Discussionmentioning
confidence: 99%